Treatments of the Noble Qur’an in supporting of Psychological Security to Face Calamities - Abdul Razzaq , Neam (Islamic Sciences Journal, 2023)
Allah Almighty revealed the Noble Qur’an to all mankind as a guide and put in it several verses that are keys to deal with life’s dilemmas and a way to escape from its trials and tribulations and guided us to methods of dealing psychologically and mentally with crises that could afflict us. This research includes some of the verses and explain their contains of educational and doctrinal guidelines that help us bear the hardships of life and be patient with its severity, so that we can enjoy great blessings in this life, after realizing the wisdom of its existence and our testing for it.